Study of Spatha Anatomical Structure of Araceae Family: A Literature Review - Qalbi, Alifa Tsamaratul (Jurnal Biologi Tropis, 2025)
Anatomical specialization in the Araceae family can use the spatha organ as a distinctive characteristic. This study is important to support the understanding of spatha structural variations that contribute to the identification and classification of Araceae plants.  This paper aims to examine the anatomical structure of the spatha of several species of Araceae. Data were collected using the literature review method by involving relevant sources from 2005-2025 obtained from Publish or Perish and Google Scholar. The data were analyzed descriptively by grouping patterns across species. The parameters observed included, (1) epidermal cell shape and (2) stomatal type. The results showed structural variations in spatha, obtained three types of epidermal cell shape and five types of stomata. Based on the literature review, it can be concluded that the anatomical variation of spatha between species of Araceae found, shows a distinctive pattern that can be used as a diagnostic character. This result is important in supporting morphological data for taxonomic purposes within the Araceae family.